1997
DOI: 10.1007/bf02684187
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of hemodynamics in aneurysm models by stenting: Influence of stent porosity

Abstract: Recent developments in minimally invasive approach to cerebrovascular diseases include the placement of stents in arteries for treatment of aneurysms. Preliminary clinical observations and experimental studies have shown that intravascular stents traversing the orifice may lead to thrombosis and subsequent occlusion of the aneurysm. The alterations in vessel local hemodynamics due to the introduction of a stent are not yet well understood. We investigated changes in local hemodynamics resulting from stent impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
174
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(187 citation statements)
references
References 12 publications
10
174
0
3
Order By: Relevance
“…Earlier studies have shown that endovascular flow diverters are capable of reducing intraaneurysmal flow and that porosity is a major determinant of this flow reduction [11,15]. The current study aimed in complementing and further extending those studies, by examining and comparing the effects of two versions (D1 and D2) of a novel low-porosity endovascular flow diverter with those from a commercially available device (Neuroform) that is already in use for clinical application.…”
Section: Summary Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies have shown that endovascular flow diverters are capable of reducing intraaneurysmal flow and that porosity is a major determinant of this flow reduction [11,15]. The current study aimed in complementing and further extending those studies, by examining and comparing the effects of two versions (D1 and D2) of a novel low-porosity endovascular flow diverter with those from a commercially available device (Neuroform) that is already in use for clinical application.…”
Section: Summary Of the Studymentioning
confidence: 99%
“…Flow patterns, velocities, pressure and their derived quantities such as shear and vorticity are made accessible by direct measurements [13,14]. Alterations of these quantities due to the insertion of a stent were quantified in previous studies by Lieber et al [11], Rhee et al [15], and Barath et al [16][17][18].…”
Section: Summary Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The porosity of a stent directly affects the amount of flow that enters an aneurysm or perforating vessel covered by the stent. Studies have found that lower-porosity stents lead to greater flow reductions within aneurysms [8,9]. To reduce stent porosity across the aneurysm (using high-porosity flexible stents), many clinicians use a stent-within-a-stent technique or "telescoping."…”
Section: Introductionmentioning
confidence: 99%
“…Various stents exhibiting four different porosities (comprised between 76 and 85%) were investigated and the results showed the difference of aneurismal vortex reduction in large and small arteries [18]. Using a photochromic dye, Rhee et al visualized the flow in sidewall and in fusiform aneurysms models, and velocity and WSS changes due to various stents could be calculated.…”
Section: Slip Stream Visualization With Devicementioning
confidence: 99%